A competing risk analysis of adherence to the American Cancer Society Guidelines on Nutrition and Physical Activity for Cancer Prevention and obesity‐related cancer risk in Hispanic/Latino adults in the NIH‐AARP Diet and Health Study. Issue 11 (23rd July 2022) - Pichardo, Margaret S.; Irwin, Melinda L.; Esserman, Denise; Molina, Yamile; Ferrucci, Leah M.
Abstract: Incidence of obesity‐related cancers (ORCs) is rising among US Hispanic/Latino adults, which may be partly due to inadequate engagement in healthy lifestyle behaviors. Prior research on cancer prevention guideline adherence and cancer risk has not considered competing events that may lead to misinterpreting the magnitude of risk between guideline adherence and cancer incidence. Among Hispanic/Latino adults (N = 9204) in the NIH‐AARP Diet and Health Study, we examined the association between adherence to the 2012 American Cancer Society (ACS) guidelines (high, moderate, low) on nutrition and physical activity for cancer prevention and risk of any first observed ORC using Fine and Gray methods for competing risk analysis. Over a median of 10.5 years of follow‐up, there were 619 first ORCs. The cumulative risk of ORC over a 15‐year period was not significantly different across ACS guideline adherence categories (high cumulative incidence function [CIF]: 2.2%‐5.8%; moderate CIF: 2.2%‐6.6%; low CIF: 2.3%‐6.7%, P Gray's log rank = .690). In competing risk analysis, high (compared to low) adherence to the ACS guidelines was associated with reduced probability of ORC (subdistribution hazard [SHR]: 0.76, 95% CI: 0.58‐0.996, P = .047), with evidence of a linear trend for increasing adherence ( P trend = .039). Our findings were consistent with hypothesized inverse associations between ACS guideline adherence and ORC incidence accounting for competing risks. These findings suggest a need for continued public health efforts focused on promoting engagement in healthy lifestyle behaviors to reduce ORC incidence among US Hispanic/Latino adults. Abstract : What's new? Using a novel competing risk framework, here the authors examine the relationship between adherence to the American Cancer Society Guidelines on Nutrition and Physical Activity for Cancer Prevention and 13 obesity‐related cancers among Hispanic/Latino adults. The analysis is one of the largest to include US Hispanic/Latino adults, a population that is disproportionately burdened by obesity and has a rising incidence of obesity‐related cancers. The findings add to the evidence that high adherence to the nutrition and physical activity guidelines may reduce the risk of obesity‐related cancers among Hispanic/Latino adults, and updates the research methodology by accounting for competing events.